1998
DOI: 10.1038/2960
|View full text |Cite
|
Sign up to set email alerts
|

A specific monovalent metal ion integral to the AA platform of the RNA tetraloop receptor

Abstract: Metal ions are essential for the folding and activity of large catalytic RNAs. While divalent metal ions have been directly implicated in RNA tertiary structure formation, the role of monovalent ions has been largely unexplored. Here we report the first specific monovalent metal ion binding site within a catalytic RNA. As seen crystallographically, a potassium ion is coordinated immediately below AA platforms of the Tetrahymena ribozyme P4-P6 domain, including that within the tetraloop receptor. Interference a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
212
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 218 publications
(223 citation statements)
references
References 38 publications
11
212
0
Order By: Relevance
“…These data are also in agreement with recent FRET results of a tethered tetraloop-receptor complex that docks in the presence of potassium (K 1/2 = 200 mM) without divalent cations (Downey et al 2006). Since crystal structures have revealed several ions closely associated with the tetraloop receptor Basu et al 1998;Golden et al 1998; FIGURE 1. Sequence and structure of the tetraloop-receptor RNA construct used in these studies.…”
Section: Ionic Dependence Of the Tetraloop-receptor Interactionsupporting
confidence: 80%
See 3 more Smart Citations
“…These data are also in agreement with recent FRET results of a tethered tetraloop-receptor complex that docks in the presence of potassium (K 1/2 = 200 mM) without divalent cations (Downey et al 2006). Since crystal structures have revealed several ions closely associated with the tetraloop receptor Basu et al 1998;Golden et al 1998; FIGURE 1. Sequence and structure of the tetraloop-receptor RNA construct used in these studies.…”
Section: Ionic Dependence Of the Tetraloop-receptor Interactionsupporting
confidence: 80%
“…The manganese associated below the AA platform (Fig. 7, site 2) is in the vicinity of a potassium binding site (Basu et al 1998), but is closer to the electron density observed by Juneau et al (2001). The NMR data suggest a divalent ion can localize to the AA platform, although the NMR observed manganese ions are on average 6.9 Å away from the potassium binding site.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…These monovalent ions are far less apt to establish a close packing of the negative charges of the nucleic acid backbone. Usually a largely unspecific role as general charge screeners is attributed to K + and Na + , even if there are also examples of specific monovalent ion binding sites ( Figure 2) [58,59]. 2+ and K + Na + and Ca 2+ levels in the cell are lower than those of Mg 2+ and K + .…”
Section: Monovalent Ionsmentioning
confidence: 99%